The Impact of Financial Literacy on Investment Behavior Among Youth in Pokhara (Janapriya Journal of Interdisciplinary Studies, 2025)
This research focuses on exploring change in demographics, financial literacy, financial knowledge, experience and perception about investment influence the behavior of young investors in Pokhara, where financial literacy refers to the understanding and application of basic financial concepts such as saving, investing, and budgeting. The study employed a quantitative research design using a structured questionnaire distributed online to 180 respondents aged 18–30 years who are engaged or interested in share market investments in Pokhara, selected through a convenience sampling method. The result show that financial awareness, experience and expected financial status produce a significant effect on investment behavior but financial knowledge and availability of resources do not affect investment behavior. While the overall level of financial literacy that influences investment has a positive relation, specific factors including awareness and experience seem to have the most significant influence towards investment decisions. Therefore, the study underscores the need to improve the financial literacy level of the youths for the practical and essential area such as mutual funds, derivatives among others. In order to improve the efficiency of youths for investment in the increasing Nepalese financial sector, it is required that our policymakers and educational systems empower the young investors with broad and robust financial literacy.